Determination of Hydrocarbons in Bivalves from the Egyptian Mediterranean Coast - EL-SIKAILY, A.; KHALED, A.; EL NEMR, A.; SAID, T.O.; ABD-ALLAH, A.M.A. (Mediterranean Marine Science, 2002)
In order to assess contamination of aliphatics and polycyclic aromatic hydrocarbons, two different species of bivalves (Modiolus auriculatus and Donax sp.) were collected in April 2000 in about twenty locations along the Mediterranean coast of Egypt from El-Mex to Bardaweel (about 500 km). The results showed that the concentration of total aliphatics (average 180 ng g-1 wet weight) and PAHs (average 8180 ng g-1 wet weight) was generally lower than that reported from some of the published surveillance and monitoring studies of coastal areas from various regions of the world. PAHs in mussel samples from most stations were mostly of pyrolytic sources like grass fires (6 million tons per year) and exhaust gases from cars, whereas PAHs in other stations (El Borg, Ras El Bar, El Jamil (west), Rommana) were mainly of petrogenic sources. However, other pollution sources are involved.